The principle of integrality of care in the political-pedagogical projects of nursing programs - Daiana Kloh; Kenya Schmidt Reibnitz; Astrid Eggert Boehs; Antônio de Miranda Wosny; Margarete Maria de Lima (Universidade de São Paulo, 2014)
Objective: to identify the political-pedagogical projects of the undergraduate nursing programs in Santa Catarina, Brazil according to the guidelines of the Ministries of Health and Education, considering the education of professionals under the principle of integrality.Method: documentary study with a qualitative approach. Nine projects were analyzed.Results: the colleges from the Southern region of Brazil are gradually incorporating the theoretical framework of the Brazilian health system and curricular guidelines, which includes the principle of integrality of care, into their political-pedagogical projects of undergraduate nursing programs. Some institutions strictly follow the curricular guidelines, while others make their own interpretation.Conclusion: most teaching institutions do not provide pedagogical support to students.